Population, economic growth and environmental emissions in Nigeria - Gambo, Lawal Suleman (2017)
This study provides empirical studies on some important issues concerning population, economic growth and environmental emissions in Nigeria over the period from 1970-2014, and the study aims to contribute to the existing literature on the effect of population growth on environmental emissions and impact of environmental emissions on economic growth. It is generally agreed that the country has a high population density and large fossil fuel resources but very poorly managed energy infrastructure which may lead to produces more carbon dioxide emissions which are a gas that is harmful to the ecosystem. Firstly, it examines the effect of population growth on the environmental emissions in Nigeria. To achieve this objective, the study was used Autoregressive distributed lag (ARDL) bounds test approach. The results for the this objective reveal that, in the short and long-run analysis, the relationship between carbon dioxide emissions and population growth, fossil fuel, and energy consumption are statistically significant and positive. In general, population growth, fossil fuel and energy consumption will eventually cause environmental emissions in Nigeria. However, the finding is consistent with the Ehrlich’s theory, which argued that overpopulation and affluence are gradually stressing the worldwide environmental emissions. Similarly, the result on the average, suggests that population control and higher oil price can also mitigate CO2 emissions and improves environmental excellence. Thus, the study recommends measures and policies to protect our physical environment. The second objective of the study examined the impact of environmental emissions on economic growth in Nigeria, specifically by employing the ARDL bounds test approach. Thus, the results for this objective also reveal that, in the short-run and long-run analysis, the relationship between economic growth and energy consumption is significant and positive. Hence, an increased in energy consumption is highly interconnected and cointegrated with the economic growth while the relationship between economic growth and foreign direct investment (FDI) and fossil fuel are significant and negative related to growth in the case of Nigeria. However, the finding is consistent with the classical theories which considered that an energy consumption as an intermediate factor for the economic growth. Thus, the results is suggested that renewable source of energy such as solar and wind could be explored and considered as an alternative source of energy since Nigeria is well endowed with solar energy. This will assist in reducing CO2 emissions and at the same time sustaining long-run growth in GDP.